Sistem Informasi Pengolahan Data Siswa di SMA Informatika Ciamis Menggunakan Microsoft Visual Basic - Rohayati, Tuti; Sidiq, Maulana; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2023)
In order to face the era of globalization, science and technology are developing rapidly, this must also be supported by qualified human resources (HR). With these quality human resources, an institution or company can make good use of technological advances, especially in the field of computers. In educational activities it is also necessary to have a computerized system for various purposes. especially in the management of student data. In SMA INFORMATIKA KABUPATEN CIAMIS, student data processing is still written directly into the main book because there is no application program that can process student data. To increase the efficiency and effectiveness of the authors make a simple application to facilitate jobs related to processing student data. Information system for processing student data will be made using Visual Basic programming and using Microsoft Access as the database. The results of this study are in the form of a student data processing information system that can help overcome problems in searching student data and student data reports.